1991
DOI: 10.1111/j.1365-2125.1991.tb03924.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pravastatin and cholestyramine on gonadal and adrenal steroid production in familial hypercholesterolaemia.

Abstract: 1. Adrenal and gonadal steroids are derived from cholesterol, which may be derived from plasma lipoproteins or de novo synthesis. 2. Inhibitors of 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMG CoA) reductase, the rate limiting enzyme in cholesterol synthesis, may therefore affect steroidogenesis when used as lipid‐lowering agents in hypercholesterolaemia. 3. We have assessed gonadal and adrenal function in subjects with heterozygous familial hypercholesterolaemia (FH) before and after 12 weeks treatment with prav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…24,27,29,30,[37][38][39][40]45,[52][53][54] Studies that included female patients found no change in ovarian steroidogenesis. 26,38,40,54 Our study confirms these findings and extends them to patients with very low levels of LDL-C. This is the first publication describing vitamin E and steroid hormone levels in patients treated with monoclonal antibodies to PCSK9.…”
Section: 22supporting
confidence: 78%
See 3 more Smart Citations
“…24,27,29,30,[37][38][39][40]45,[52][53][54] Studies that included female patients found no change in ovarian steroidogenesis. 26,38,40,54 Our study confirms these findings and extends them to patients with very low levels of LDL-C. This is the first publication describing vitamin E and steroid hormone levels in patients treated with monoclonal antibodies to PCSK9.…”
Section: 22supporting
confidence: 78%
“…35,36 The impact of statins on adrenal function has been studied in multiple populations with a wide variety of statins. 23,[25][26][27][28][29]31,32,[37][38][39][40][41][42][43][44][45] None of these studies showed clinically relevant impairment of adrenal function, secondary to statin therapy. Patients with heterozygous or homozygous familial hypercholesterolemia could also theoretically be at increased risk of adrenal dysfunction because of their reduced capacity to use LDL receptor-mediated cholesterol uptake.…”
Section: 22mentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with the data from studies evaluating the effect of long-term statin therapy on gonadal and adrenal steroid production in adults. 32,33 The hypothalamic feedback factors (LH and FSH) for the gonadal hormones were difficult to evaluate because of the great variability and large proportion of nondetectable plasma levels. However, Tanner stage, testicular volume, and menstrual cycle length exhibited the normal pattern, and simvastatin (40 mg) did not appear to …”
Section: Growth and Sexual Maturationmentioning
confidence: 99%